Productivity Constraints in Arid Land Agriculture - Singh, Punjab (Annals of Arid Zone, 2016)
The lack of management and methods of crop cultivation have rendered most of the arid lands unproductive. Inspite of several scientific achievements, the productivity on these lands continues to be more or less static at a lower level and dependent on monsoon. On the other hand, the yields from research farms and from National Demonstration Trials conducted at farmers fields have shown much higher production potentials on these lands which essentially suggests to bridge the gap between the obtained and obtainable levels of productivity. Many-fold increase in biomass production on these lands through proper management, besides increasing total food grain production, will be one among the many ways suggested to check the march of the desert through its various meritorious effects. In this paper some such steps have been detailed.